UNIVERSAL GREASING AND MODIFICATING SUBSTANCE FOR FOUNDRY AND METAL-WORKING PRODUCTION - A. A. Klyshko (Литьë и металлургия)
The characteristic of new universal lubricating and modifying stuff for foundry and metal-working production is given in the article.